Stereotactic Ablative Radiation Therapy for the Treatment of Early-stage Non–Small-Cell Lung Cancer. Issue 6 (June 2015) - Boily, Gino; Filion, Édith; Rakovich, George; Kopek, Neil; Tremblay, Lise; Samson, Benoit; Goulet, Stéphanie; Roy, Isabelle
<x xml:space="preserve">Abstract</x> Background: Lung cancer is the second most diagnosed cancer and the leading cause of cancer-related mortality in Canada. Surgical resection is the treatment of choice for patients with stage I non–small-cell lung cancer (NSCLC). However, 20% to 30% of them are deemed medically inoperable and may be offered radiation therapy. Standard external-beam radiation therapy (EBRT) is associated with high rates of local recurrence and poor long-term survival. Stereotactic ablative radiation therapy (SABR) is increasingly being proposed for inoperable patients, and the use of this treatment modality for operable patients is also being contemplated. The objective of this guideline is to review the efficacy and safety of SABR in these two clinical situations and to develop evidence-based recommendations. Method: A review of the scientific literature published up to December 2013 was performed. A total of 44 publications were included. Recommendations: Considering the evidence available to date, the Comité de l'évolution des pratiques en oncologie recommends the following: (1) for medically operable patients with stage T1-2N0M0 NSCLC, surgery remains the standard treatment because comparative data regarding the efficacy of SABR and surgery are currently insufficient for SABR to be considered an equivalent alternative to surgery for these patients; (2) for medically inoperable patients with stage T1-2N0M0 NSCLC or medically operable patients who refuse surgery, SABR should be preferred to standard EBRT (grade B recommendation); (3) the biological equivalent dose (BED10) used for SABR treatment should be at least 100 Gy (grade B recommendation); (4) for patients with a central tumor, a large-volume tumor (large planning target volume) or severe pulmonary comorbidity, a risk-adaptive schedule should be used (dose reduction or increase in the number of fractions; grade B recommendation); (5) the choice of using SABR to treat NSCLC should be discussed within tumor boards; treatment with SABR (or with standard EBRT) should not be considered for patients whose life expectancy is very limited because of comorbidities (grade D recommendation).